CONTEMPORARY ASPECTS OF LEGAL APPROXIMATION BETWEEN THE EUROPEAN UNION AND THE RUSSIAN FEDERATION (EU and comparative law issues and challenges series (ECLIC), 2020)
Legal harmonization has been playing a central part in international relations from the second half of the XX century. This was caused by the intensification of cooperation in the economic sphere between both public and private actors from different countries. This can be seen in an example of the European Union and the Russian Federation. The goal of legal approximation of the EU law with the Russian legal system was inscribed in the Partnership and Cooperation Agreement between the European Communities and the Russian Federation. Russia, like many countries that are not member states of the European Union, has been making efforts to approximate their national legislation to norms of the EU legal system. Legislative approximation of the EU law means transposition, implementation, and enforcement of the norms of the EU legal system in their partner countries’ national legal practices; a legislative process that aims gradually to bring closer and eventually to bring into compliance partner countries’ legislative framework with EU law. The research is focused on the study of modern issues of approximation between legal orders of the European Union and the Russian Federation with stress on particular branches of law, which was influenced by the process. The author starts from the evolution of the approximation process, its general issues, development of a relevant international legal basis. Features of influence of the EU on developments of the Russian legal system were identified and analyzed. As the EU-Russia legal approximation process now faces both internal and external-global threats, relevant law, developments of its different spheres and branches of the legal system of the Russian Federation, will be explored. In the focus of research, there will be developments in the following branches: civil law, labor law, technical regulation, legal regulation of higher education. The author finally gives his view on prospects of the EU-Russia legal approximation process, its development in the light of existing and future global and regional challenges and relations.